A study on the relationship between dividend yield, trading volume and price earning ratio with stock price / Siti Zaleha Zainudin - Zainudin, Siti Zaleha (2005)
This study further examines the relationship between stock prices with dividend yield, trading volume and price earning ratio that concentrate on the shares listed in the Main Board at Bursa Malaysia. This study was done because of the controversy opinions about the relationship between stock prices with dividend yield, trading volume and price earning ratio. The sample consists of stock prices, dividend yield, trading volume and price earning ratio of 31 Industrial Product companies in Bursa Malaysia Main Board and it is monthly data from 1999 to 2003. Tools such as Regression Model, Correlation Coefficient and R Square were used to test the correlation between dependent and independent variables, while T-Statistic and F-Statistic were used to test the significance between dependent and independent variables. The findings ending with a result, which found that, there is a significant relationship trading volume and stock price. However, another result found that there are no significant relationship between dividend yield and price earning ratio with stock prices